The aerospace business : management and technology - Spreen, Wesley E. (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This textbook provides a detailed overview of industry-specific business management and technology management practices in aerospace for relevant bachelors and MBA programs. The Aerospace Business: Management and Technology sequentially addresses familiar management disciplines such as production management, labor relations, program management, business law, quality assurance, engineering management, supply chain management, marketing, finance, among others. In this context it analyzes and discusses the distinctive perspective and requirements of the aerospace industry. The book also includes subjects of special interest such as government intervention in the sector and strategies to deal with the environmental impact of aircraft. As each chapter deals with a separate management discipline, the material reviews the historical background, technical peculiarities, and financial factors that led the aerospace industry to evolve its own distinct practices and tradition. Theoretical bases of the practices are explained, and the chapters provide actual examples from the industry to illustrate application of the theories. The material is compiled, organized, and analyzed in ways that often provide original perspectives of the subject matter. University students, particularly in programs oriented towards aviation and aerospace management, will find the book to be directly applicable to their studies. It is also extremely appropriate for aerospace MBA and executive MBA programs, and would suit specialized corporate or government training programs related to aerospace"--
OCLC-licensed vendor bibliographic record.
Keywords: Aerospace industries -- Management; TRANSPORTATION / Aviation / Commercial